Climate Change and the Right to Safe and Clean Water in Nakivale Refugee Settlement, Insigiro District. - Flavia Mercy Apiyo (Uganda Christian University, 2023)
This study was about Climate Change and the Right to Safe and Clean Water in Nakivale Refugee Settlement, Isingiro District. The study was prompted by the desire to assess climate change and its implications towards the availability, accessibility, right to access clean and safe water and as well as to find out the existing copying strategies established by refugees Nakivaale settlement The study was undertaken using a mixed methods approach and that is to say; descriptive qualitative and analytical quantitative designs. The sample population comprised of 60 respondents and this included the sample size of 30 Refugees, 10 humanitarian workers, 7 Community Leaders, 6settlement Health Workers, 4 NGO Representatives, and 3 Government Officials. The selection strategy was through, simple random sampling and purposive sampling. The researcher employed basically two tools for data collection. That is; questionnaires and interview guide to collect data. After collection of the data, the results were analyzed in form of statistical tables, percentages as well as pie charts to give good visual impression. The research findings indicate that, Clean and safe water is still a challenge in Nakivale Refugees’ Settlement as clean and safe water is not readily available for the people in the settlement and there are no clear access routes to fetch clean and safe water. This is further worsened by the situation of Clean and safe water that cannot easily be gotten by even women and children within the settlement. The utilization of polluted water enhanced by climate change has led to water borne disease in Nakivale Refugees’ Settlement because due to scarcity of water, the majority of people within the settlement have resorted to not only sharing water sources like lakes, dams and swamps with animals but consuming polluted water in the settlement. Finally, the study recommends that, the government, NGOs and all other stakeholders supporting refugees in Nakivale settlement should increase budget allocation for clean and safe water, Encourage and support refugees to build local cemented tanks for the preservation of rain water during drought, creation of small dams where animals can drink water from , provision of water-guard tablets to treat water before utilization and extent more taps in villages to reduce on the long queues which are causing conflicts and fights due to frustrations while at the water sources.
This is a dissertation.